Investment in exploration and exploitation in hydrocarbons and collection of the income tax in Peru - Oscanoa Ponce, Bill Frank (2018)
The investigation allowed to establish the relation between the investments in exploration and exploitation in Hydrocarbons and the collection of the Income Tax in Peru during the period 2000-2016. Based on this objective, a descriptive analysis was performed on the relationship between the variables and an inferential analysis: the Pearson correlation coefficient and the simple linear regression. Thus, the main results obtained show that there is a relation between the investments in exploration and exploitation in Hydrocarbons and the collection of the Income Tax, and that the degree of this relationship is strong. In addition, it was found that the sense of the relationship is positive and statistically significant. Thus, it was concluded that higher levels of investment in exploration and exploitation in Hydrocarbons higher levels of income tax collection. Thus, it is recommended to the Peruvian State in a sectoral crisis context to establish an Investment Plan so that consequently obtain an adequate.